Eco-friendly marketing analysis on sustainable purchase intentions for Skincare brands the Bodyshop, Avoskin and N'Pure - Bafadal, Amalia; Roostika, Ratna (Universitas Ahmad Dahlan, 2025)
This study aims to analyze the influence of eco-friendly marketing on sustainable purchase intentions for skincare products from The Body Shop, Avoskin, and N'pure. A quantitative approach was used with a survey method involving 229 skincare users in Indonesia. Data were collected through a questionnaire using a Likert scale and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results show that (1) Perceived Sustainable Marketing Activities positively affect brand image; (2) Brand image negatively affects sustainable purchase intentions; (3) Brand image positively affects consumer engagement; (4) Consumer engagement positively affects sustainable purchase intentions; and (5) Corporate Social Responsibility (CSR) positively affects sustainable purchase intentions. This study contributes to the development of marketing literature by highlighting the mediating role of consumer engagement in eco-friendly marketing. Practically, the findings suggest that to strengthen sustainable purchase intentions, companies need to ensure alignment between their brand image and real environmental and social initiatives.